Charter to commemorate the "Great Demonstration" in London on February 11th, 1867 and the meeting of 22,000 persons inthe Agricultural Hall
Charter to commemorate the "Great Demonstration" in London on February 11th, 1867 and the meeting of 22,000 persons inthe Agricultural Hall.